A critique of the drive towards the globalization of higher education - David Bird; Brian Nicholson (Association for Learning Technology, 1998)
There has been an increase in the level of commerce that transcends national boundaries. Businesses no longer rely on local markets as acceptable, safe areas to do business. The emphasis is on globalization. Failing to globalize will result in the decline of a commercial activity, and a 1990 survey among businesses found that 40 per cent of them considered the expansion of the global market required increased production capacity and speed (Peppard, 1993).